Creating and dominating new markets - Meyer, Peter, 1954- (New York : AMACOM, 2002)
Publisher Fact Sheet Offers managers, executives, and business strategies to emulate the success of savvy market creators such as Microsoft, FedEx, and AOL.
Part 1 Strategies for Creating and Dominating New Markets 1 -- Part 2 Applications of the Strategies 111.
Includes bibliographical references (pages 227-232) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: New products; Marketing; Creative ability in business; Marketing; Marketing; Créativité dans les affaires; marketing; BUSINESS & ECONOMICS -- Marketing -- General; BUSINESS & ECONOMICS -- Distribution; Creative ability in business; Marketing; New products